EFL secondary school teachers’ conceptions of online assessment in emergency remote teaching: A phenomenographic study - Roghibatul Luthfiyyah; Bambang Yudi Cahyono; Francisca Maria Ivone; Nunung Suryati (Studies in English Language and Education, 2022)
The investigation of teachers' conceptions of online assessment during a global pandemic has received relatively scarce attention in the current literature. Situated in an emergency remote teaching, this phenomenographic study aims at identifying and describing EFL secondary school teachers' qualitative different ways of understanding online assessment. A cohort of fifteen EFL teachers from different Indonesian secondary schools were recruited purposively using a set of criteria. They were invited to involve in online semi-structured interviews to explore their online assessment conceptions. Then, the interview data were analyzed qualitatively in an iterative process to discern categories of description and an outcome space. The findings point out five categories of teachers' conceptions. The participants view online assessment in emergency remote teaching (ERT) as a means of (1) measuring knowledge, (2) checking learning targets, (3) enhancing online interaction, (4) facilitating authentic tasks, and (5) reflecting the teaching and learning process. Furthermore, an analysis of relationships among those categories is reported hierarchically, ranging from accountability to enhancement assessment purposes. Some implications promote our understanding to consider several mediating factors affecting teachers' conceptions. Although emergency remote teaching situation is provisional, the findings bring out the possibility of implementing assessment for learning, as an alternative to assessment of learning, in the context of online assessment after the pandemic.